Association between chronic kidney disease and physical activity level in patients with ischemic heart disease - Matsuzawa, Ryota; Masuda, Takashi; Kamiya, Kentaro; Hamazaki, Nobuaki; Nozaki, Kohei; Tanaka, Shinya; Maekawa, Emi; Ako, Junya (Renal replacement therapy, 2017)
Background Although it is believed that chronic kidney disease (CKD) in patients with ischemic heart disease (IHD) negatively affects physical activity after discharge, its actual influence on the physical activity of patients with IHD remains unclear. This study aimed to investigate the association between CKD and the acquirement of appropriate physical activity after hospital discharge in patients with IHD. Methods Subjects were 245 patients with IHD (65 ± 11 years, 203 males) admitted to Kitasato University Hospital from July 2007 to January 2014 due to unstable angina pectoris or acute myocardial infarction. Appropriate physical activity was defined according to the American Heart Association/the American College of Cardiology guidelines, which recommend ≥150 min/week of moderate-to-vigorous activity. We assessed intervention for IHD, comorbidities, smoking habits, serum high-sensitivity C-reactive protein, estimated glomerular filtration rate (eGFR), left ventricular ejection fraction, duration of hospital stay, 6-min walk distance during hospitalization, and physical activity 3 months after discharge. Patients with eGFR ≥60 mL/min/1.73 m 2 and 15 ≤ eGFR < 60 mL/min/1.73 m 2 were diagnosed with stage G1-G2 CKD and stage G3-G4 CKD, respectively. Results Only 87 patients (35.5%) achieved appropriate levels of physical activity. Stepwise multivariate logistic regression analysis identified stage G3-G4 CKD (odds ratio, 1.91; 95%CI, 1.02–3.55; P = 0.04) and a 6-min walk distance <400 m (odds ratio, 17.8; 95%CI, 4.16–76.6; P < 0.001) as significant independent factors that hinder acquiring appropriate physical activity. Conclusions Stage G3-G4 CKD was associated with poor acquirement of appropriate physical activity after hospital discharge in patients with IHD.